Potential structural and functional biomarkers of upper motor neuron dysfunction in ALS. Issue 1 (17th February 2016) - Grieve, Stuart M.; Menon, Parvathi; Korgaonkar, Mayuresh S.; Gomes, Lavier; Foster, Sheryl; Kiernan, Matthew C.; Vucic, Steve
Abstract: Assessment of upper motor neuron (UMN) function in amyotrophic lateral sclerosis (ALS) remains clinically based. Given the potential difficulties in identifying UMN signs, objective biomarkers of UMN dysfunction are important. Consequently, the present study assessed utility of cortical thickness analysis combined with threshold tracking transcranial magnetic stimulation (TMS) as biomakers of UMN dysfunction in ALS. Cortical thickness analysis and threshold tracking TMS studies were undertaken on 25 ALS patients and results were compared to healthy control subjects, with different control groups used for each technique. Structural and functional abnormalities were evident in both motor cortices in the ALS cohort and were heralded by marked reduction of short-interval intracortical inhibition (SICIRAPB 1.4 ± 2.4%; SICILAPB 3.6 ± 1.9%; SICICONTROLS 10.5 ± 1.1%, p  <0.01), resting motor threshold ( p  <0.05) and cortical silent period duration ( p  <0.001) combined with increase in MEP amplitude ( p  <0.05) and intracortical facilitation ( p  <0.05). Significant cortical thinning was evident in the bitemporal regions ( p  <0.05), while precentral gyrus cortical thinning was evident in 56% of cases and when combined with TMS abnormalities disclosed UMN dysfunction in 88% of cases. In conclusion, findings from the present study establish that a combination of structural and functional assessment of corticomotoneurons may increase the yield of objectively identifying UMN dysfunction in ALS.